2005
DOI: 10.1128/aem.71.1.255-260.2005
|View full text |Cite
|
Sign up to set email alerts
|

Redox Interactions betweenSaccharomyces cerevisiaeandSaccharomyces uvarumin Mixed Culture under Enological Conditions

Abstract: Wine yeast starters that contain a mixture of different industrial yeasts with various properties may soon be introduced to the market. The mechanisms underlying the interactions between the different strains in the starter during alcoholic fermentation have never been investigated. We identified and investigated some of these interactions in a mixed culture containing two yeast strains grown under enological conditions. The inoculum contained the same amount (each) of a strain of Saccharomyces cerevisiae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Another possible cause for such an apparent decreased ability to regenerate NAD + may be the inhibitory effect of ethanol at the level of the mitochondrial respiratory chain, whose function depends deeply on membrane integrity. Strongly linked with the intracellular redox status is the type and amount of by-products formed during yeast metabolism [44], [45], [50], [51], [52], [53]. Indeed, the exo-metabolome analysis carried out herein showed a higher accumulation in the broth medium of acetate, pyruvate, acetoin and acetaldehyde when ethanol is exogenously added, in a dose dependent way.…”
Section: Discussionmentioning
confidence: 62%
“…Another possible cause for such an apparent decreased ability to regenerate NAD + may be the inhibitory effect of ethanol at the level of the mitochondrial respiratory chain, whose function depends deeply on membrane integrity. Strongly linked with the intracellular redox status is the type and amount of by-products formed during yeast metabolism [44], [45], [50], [51], [52], [53]. Indeed, the exo-metabolome analysis carried out herein showed a higher accumulation in the broth medium of acetate, pyruvate, acetoin and acetaldehyde when ethanol is exogenously added, in a dose dependent way.…”
Section: Discussionmentioning
confidence: 62%
“…Cheraiti et al (2005) showed that the maximum population of a mixed culture of S. cerevisiae and a S. cerevisiae x S.…”
Section: Positive Interactionsmentioning
confidence: 99%
“…During storing and aging of wine, oxidation and reduction processes affect the character and taste of wine to a considerable extent [11,12]. We surmise that the same features could occur in the case of Mezcal making.…”
Section: Redox Potentialmentioning
confidence: 99%
“…Previously, various attempts of relating the redox potential to fermentation processes have been made taking into account that redox potential assesses the growth ability of microorganisms, as well as the physiological activity in a given environment [8][9][10][11]. Particularly, the practical significance of redox potential and oxygen content at various stages of winemaking was examined in Ref.…”
Section: Introductionmentioning
confidence: 99%